APPLICATION OF THE NAÏVE BAYES ALGORITHM FOR PREDICTION OF LUNG DISEASES USING RAPIDMINER - Muhammad Rafi Muttaqin; Imam Ma'ruf Nugroho; Moch. Hafid; Muhyidin, Yusuf (Sekolah Tinggi Teknologi Wastukancana, 2024)
The lungs are the main organ in the human respiratory system which is located in the chest cavity and consists of a pair. The lungs are a vital organ that greatly influences the body's health, because it has the function of maintaining the body's acid-base balance, removing carbon dioxide that the body does not need and water vapor. Smoking is the main cause of lung disease, in 2020 based on the World Health Organization (WHO) report, it is estimated that 10 million people suffer from lung disease worldwide. This research uses the Naïve Bayes classification algorithm to obtain a prediction model that can predict lung disease patient data. This research aims to obtain accuracy values ​​using the Naïve Bayes algorithm. The data used in this research was obtained from Kaggle which contains 469 data with 14 attributes in it. RapidMiner is used as a tool to test the patient dataset used to produce a prediction with an accuracy rate of 99.9% risk false (no risk of having lung disease).